2022
DOI: 10.2174/1389200224666221212143904
|View full text |Cite
|
Sign up to set email alerts
|

Covalent CES2 Inhibitors Protect against Reduced Formation of Intestinal Organoids by the Anticancer Drug Irinotecan

Abstract: Background: Irinotecan is widely used to treat various types of solid and metastatic cancer. It is an ester prodrug and its hydrolytic metabolite (SN-38) exerts potent anticancer activity. Irinotecan is hydrolyzed primarily by carboxylesterase-2 (CES2), a hydrolase abundantly present in the intestine such as the duodenum. We have identified several potent and covalent CES2 inhibi¬tors such as remdesivir and sofosbuvir. Remdesivir is the first small molecule drug approved for COVID-19, whereas sofosbuvir is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…Different from CES1, CES2 is mainly expressed in the small intestine and also expressed to a lesser extent in the kidney, liver, heart, brain, and testis (Figure 2) (Satoh et al, 2002;Taketani et al, 2007;Sanghani et al, 2009). CES2 substrates include acebutolol, aspirin, flupirtine, flutamide, heroin, irinotecan, gemcitabine (Pratt et al, 2013), doxazolidine (Barthel et al, 2009), molnupravir (Shen et al, 2022), and capecitabine (Quinney et al, 2005) (Table 1). Similar to CES1, CES2 expression and activity can be regulated by both genetic and nongenetic factors.…”
Section: Carboxylesterase 2 (Ces2)mentioning
confidence: 99%
“…Different from CES1, CES2 is mainly expressed in the small intestine and also expressed to a lesser extent in the kidney, liver, heart, brain, and testis (Figure 2) (Satoh et al, 2002;Taketani et al, 2007;Sanghani et al, 2009). CES2 substrates include acebutolol, aspirin, flupirtine, flutamide, heroin, irinotecan, gemcitabine (Pratt et al, 2013), doxazolidine (Barthel et al, 2009), molnupravir (Shen et al, 2022), and capecitabine (Quinney et al, 2005) (Table 1). Similar to CES1, CES2 expression and activity can be regulated by both genetic and nongenetic factors.…”
Section: Carboxylesterase 2 (Ces2)mentioning
confidence: 99%
“…Carboxylesterases constitute a large class of serine hydrolases with high catalytic efficiency. In humans, CES1 and CES2 are two c arboxyl es terases with known pharmacological and toxicological significance 106–109 . These two carboxylesterases, on the other hand, differ in their substrate specificity and tissue distribution 110–112 .…”
Section: Metabolism and Active Transportmentioning
confidence: 99%
“…Remdesivir, on the other hand, is hydrolytically activated, and the hydrolysis is catalyzed by CES1 96 . At the same time, remdesivir is a covalent inhibitor of CES2, 97 a hydrolase that therapeutically activates molnupiravir 98,106 . It has been shown that the expression of CES1 is inversely correlated with the inhibition of CES2, suggesting that remdesivir but not its hydrolytic metabolite is a CES2 inhibitor.…”
Section: Potential Of Combined Use Of Small Molecule Covid‐19 Medicinesmentioning
confidence: 99%
See 2 more Smart Citations